Calculating singlet excited states: comparison with fast time-resolved infrared spectroscopy of coumarins - Hanson-Heine, Magnus W.D.; Wrigglesworth, Alisdair; Uroos, Maliha; Calladine, James A.; Murphy, Thomas S.; Hamilton, Michelle; Clark, Ian P.; Towrie, Michael; Dowden, James; Besley, Nicholas A.; George, Michael W. (American Institute of Physics, 2015)
In contrast to the ground state, the calculation of the infrared (IR) spectroscopy of molecular singlet excited states represents a substantial challenge. Here we use the structural IR fingerprint of the singlet excited states of a range of coumarin dyes to assess the accuracy of density functional theory based methods for the calculation of excited state IR spectroscopy. It is shown that excited state Kohn-Sham density functional theory provides a high level of accuracy and represents an alternative approach to time-dependent density functional theory for simulating the IR spectroscopy of the singlet excited states.